Armazenagem de hidrogênio em cavacos de magnésio produzidos por meio de usinagem criogênica - Déo, Filipe Ferrari Galan (Universidade Federal de São Carlos, 2021)
Hydrogen is a clean and low cost fuel, and its storage on solid state shows out to be a possibility for large scale application. Magnesium is considered a good material for hydrogen storage due to some interesting features of magnesium hydride, and several studies were held to enhance its capacity for hydrogen absorption and desorption. Cryogenic machining is considered as an possible alternative to develop kinetics on this material, also responsible for enhancing properties of the machined parts and helping machining process. This degree final project aims to analyze the effect of cryogenic machining over hydrogen storage on magnesium chips. Shaping operation was used regarding an orthogonal cutting in order to facilitate the process analysis and chip formation, using both pure magnesium and AZ31 commercial alloy, both on dry and cryogenic conditions. Chips obtained were analyzed by scanning electron microscopy and X-ray diffraction in order to evaluate crystallographic texture and morphology. Deformation factor, shear angle, strain and strain rate were calculated and compared between specimens. Finally, two cycles of hydrogenation in each sample in order to obtain absorption and desorption curves, which were also compared. Results show that, although chips from the same material presented equal crystallographic texture and morphology, also the same calculated parameters, absorption and desorption kinetics were better when cryogenic machining was employed for the AZ31 magnesium alloy. It is believed that machining strain on low temperatures may be responsible for grain refinement on the chip, which ensures better hydrogen kinetics. Finally, it is possible that this research area may be promising, as new analysis might be developed in order to employ hydrogen as a clean fuel in large scale.
Hydrogen storage on magnesium chips after cryogenic machining
Keywords: Combustível; Hidreto de magnésio; Aplainamento; Deformação; Refinamento de grão; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO